Canalization and Developmental Instability of the FetalSkull in a Mouse Model of Maternal Nutritional Stress - Gonzalez, Paula Natalia (2014)
Nutritional imbalance is one of themain sources of stress in both extant and extinct humanpopulations. Restricted availability of nutrients isthought to disrupt the buffering mechanisms that con-tribute to developmental stability and canalization,resulting in increased levels of fluctuating asymmetry(FA) and phenotypic variance among individuals. How-ever, the literature is contradictory in this regard. Thisstudy assesses the effect of prenatal nutritional stresson FA and among-individual variance in cranial shapeand size using a mouse model of maternal proteinrestriction. Two sets of landmark coordinates were digi-tized in three dimensions from skulls of control and pro-tein restricted specimens at E17.5 and E18.5. We foundthat, by the end of gestation, maternal protein restric-tion resulted in a significant reduction of skull size.Fluctuating asymmetry in size and shape exceeded theamount of measurement error in all groups, but no sig-nificant differences in the magnitude of FA were foundbetween treatments. Conversely, the pattern of shapeasymmetry was affected by the environmental perturba-tion since the angles between the first eigenvectorsextracted from the covariance matrix of shape asymmet-ric component of protein restricted and control groupswere not significantly different from the expected forrandom vectors. In addition, among-individual variancein cranial shape was significantly higher in the proteinrestricted than the control group at E18.5. Overall, theresults obtained from a controlled experiment do notsupport the view of fluctuating asymmetry of cranialstructures as a reliable index for inferring nutritionalstress in human populations.